Chloroform-softened gutta-percha with zoe sealer and gutta-percha with zoe sealer mixed with chloroform against standard gutta-percha with zoe sealer A comparative study - Arellano, Ma. Victoria A.; Laureta, Joaquin G.; Porter, Irene A. (Adviser).
This study compared the effect on apical seals between two ways of using chloroform in obturation against the standard gutta-percha with ZOE sealer technique. Measurement of apical leakage patterns revealed that chloroform-softened gutta percha with ZOE sealer produced the least mean apical leakage followed by the standard gutta-percha with ZOE sealer. Gutta percha with ZOE sealer mixed with chloroform produced the greatest mean apical leakage value.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Gutta-percha.; Chloroform